2019
DOI: 10.1016/j.infpip.2019.100009
|View full text |Cite|
|
Sign up to set email alerts
|

Outbreak of Acinetobacter baumannii associated with extrinsic contamination of ultrasound gel in a tertiary centre burn unit

Abstract: Summary Background During 2011 and 2012, an increase in occurrence of multidrug-resistant Acinetobacter baumannii infections was recorded in the Shands Hospital Burn Intensive Care Unit (BICU). An epidemic curve together with strain typing was consistent with an intermittent common source outbreak. An investigation was therefore initiated. Aim To identify risk factors for A. baumannii infection, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As the number of patients with difficult access increases, UGPIV becomes a standard solution and procedure for establishing intravenous access. However, ultrasound probes and gels are common sources of contamination, requiring recommendations for probe protection for percutaneous vascular access procedures [9,12]. Aseptic techniques, probe protection, barrier methods, and incorporation of single-use or sterile gel packets are used to safeguard against insertion site contamination [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the number of patients with difficult access increases, UGPIV becomes a standard solution and procedure for establishing intravenous access. However, ultrasound probes and gels are common sources of contamination, requiring recommendations for probe protection for percutaneous vascular access procedures [9,12]. Aseptic techniques, probe protection, barrier methods, and incorporation of single-use or sterile gel packets are used to safeguard against insertion site contamination [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…The use of conductive gel is problematic because it is often contaminated during ultrasound procedures and can introduce pathogens at the insertion site. Infection outbreaks have identified gel contamination as the mode of transmission in numerous reports [9]. Single-use, sterile gel packets are recommended for percutaneous procedures where the gel is applied to the skin, with probe covers requiring gel [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we reported an outbreak of OXA-23 and PER-1 XDR-Ab with probable environmental origin during a period not exceeding two months. A. baumannii remains one of the highest causes of outbreaks in BICU [18] and most of them have been traced to environmental sources [19]. The ability of A. baumannii to form biofilms on abiotic surfaces, its high degree of resistance to drying and disinfectants and its ability to develop resistance to commonly used antimicrobial agents, lead to its long term persistence in the environmental setting [20].…”
Section: Discussionmentioning
confidence: 99%
“…Species belonging to the Acinetobacter genus are strictly-aerobic, non-fermentative Gram-negative coccobacilli, predominantly found in water, soil, and sewage. Over 50 different species of Acinetobacter genus are known, but only a few species, belonging to the A. calcoaceticus-baumannii complex, cause the majority of community and healthcare associated infections [ 1 , 2 , 3 ]. A. baumannii is considered an opportunistic pathogen, and risk factor for developing an infection include mechanical ventilation, prolonged hospitalization, immune suppression, comorbidities, major trauma or burns, previous antibiotic use, invasive procedures, and presence of urinary catheters [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 50 different species of Acinetobacter genus are known, but only a few species, belonging to the A. calcoaceticus-baumannii complex, cause the majority of community and healthcare associated infections [ 1 , 2 , 3 ]. A. baumannii is considered an opportunistic pathogen, and risk factor for developing an infection include mechanical ventilation, prolonged hospitalization, immune suppression, comorbidities, major trauma or burns, previous antibiotic use, invasive procedures, and presence of urinary catheters [ 1 , 2 , 3 , 4 ]. A. baumannii can be transmitted via aerosol droplets, person-to-person contact, skin, sputum, urine, and feces [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%